The Effectiveness of a Decotion of Green Betel Leaf (Piper bettle L) in Treating Vaginal Discharge in Women of Childbearing Age (Wus) - Filda Fairuza; Rina Octavia (POLTEKKES KEMENKES PONTIANAK, 2026)
Vaginal discharge is a common reproductive health issue experienced by women of childbearing age and can cause discomfort and increase the risk of reproductive health problems if not properly managed. One widely used non-pharmacological treatment option is a decoction of green betel leaf (Piper betle L.), as it contains active compounds such as flavonoids, tannins, saponins, and essential oils that possess antiseptic, antibacterial, and antifungal properties. This study aims to analyse the effectiveness of green betel leaf decoction against vaginal discharge in women of childbearing age at the Kimia Farma BSD Clinic in 2025. The study employed a quasi-experimental design using a one-group pretest-posttest approach. The study sample comprised 36 women of childbearing age experiencing vaginal discharge, selected using purposive sampling. The intervention involved the use of green betel leaf decoction for 10 days. Data were collected via questionnaires before and after the intervention, then analysed using the Wilcoxon Signed-Rank test with a significance level of 5%. The results of the study showed a reduction in the incidence of vaginal discharge following the intervention, as indicated by an increase in the number of respondents who did not experience vaginal discharge and a decrease in the number of respondents with pathological vaginal discharge. Statistical analysis revealed a significant difference between the pre- and post-intervention conditions (p<0.05). Thus, a decoction of green betel leaves (Piper betle L.) has been proven effective in reducing symptoms of vaginal discharge in women of reproductive age and has the potential to serve as a safe, simple, and easily applicable non-pharmacological therapeutic alternative.